Phosphodiesterase-2 Inhibitor Bay 60-7550 Ameliorates Aβ-Induced Cognitive and Memory Impairment via Regulation of the HPA Axis - Ruan, Lina; Du, Kai; Tao, Mengjia; Shan, Chunyan; Ye, Ruixuan; Tang, Yali; Pan, Hanbo; Lv, Jinpeng; Zhang, Meixi; Pan, Jianchun (Frontiers in Cellular Neuroscience, 2019)
The dysfunction of the hypothalamus-pituitary-adrenal (HPA) axis is often seen in Alzheimer’s disease (AD) patients with cognitive deficits. Selective inhibition of phosphodiesterase (PDE) 4 and 5 has already proven to be effective in reducing beta-amyloid 1-42 (Aβ1-42)-mediated pathology by regulating corticotropin-releasing factor (CRF) and glucocorticoid receptors (GR) expression, suggesting that PDE-dependent signaling is involved in Aβ1-42 induced HPA axis dysfunction. However, nausea and vomiting are the side effects of some PDE4 inhibitors which turn our attention to other PDEs. PDE2 are highly expressed in the hippocampus and cortex,which associate with learning and memory, but not in the area postrema that would cause vomiting. The present study suggested that microinjection of Aβ1-42 to the intracerebroventricle induced learning and memory impairments and dysregulation of the HPA axis by increased expression of CRF and GR. However, PDE2 inhibitor Bay 60-7550 significantly ameliorated the learning and memory impairment in the Morris water maze and step-down passive avoidance tests. The Aβ1-42-induced increased CRF and GR levels were also reversed by the treatment with Bay 60-7550. These Bay 60-7550’s effects were prevented by pretreatment with PKG inhibitor KT5823. Moreover, the Bay 60-7550-induced downstream pCREB and BDNF expression was also prevented (or partially prevented) by KT5823 or PKA inhibitor H89. These results maylead to the discovery of novel strategies for the treatment of age-related cognitive disorders, such as Alzheimer’s disease, which affects approximately 44 million people worldwide.